After Kyoto: Alternative Mechanisms to Control Global Warming - Nordhaus, William D (American Economic Review, 2006)
After more than a decade of negotiations and planning under the Framework Convention on Climate Change (FCCC), the first binding international agreement to control the emissions of greenhouse gases has come into effect in the Kyoto Protocol. The first budget period of 2008–2012 is at hand. Moreover, the scientific evidence on greenhouse warming strengthens steadily as observational evidence of warming accumulates. The institutional framework of the Protocol has taken hold solidly in the European Union’s Emissions Trading Scheme (ETS), which covers almost half of Europe’s carbon dioxide emissions. Notwithstanding this apparent success, the Kyoto Protocol is widely seen as somewhere between troubled and terminal. Early troubles came with the failure to include the major developing countries along with lack of an agreedupon mechanism to include new countries and extend the agreement to new periods. The major blow came when the United States withdrew from the treaty in 2001. By 2002, the Protocol covered only 30 percent of global emissions, while the hard enforcement mechanism in the ETS accounts for about 8 percent of global emissions. Even if the current Protocol is extended, models indicate that it will have little impact on global temperature change. Unless there is a dramatic breakthrough or a new design, the Protocol threatens to be seen as a monument to institutional overreach. Nations are now beginning to consider the structure of climate-change policies for the period after 2008 to 2012. Some countries, states, cities, companies, and even universities are adopting their own climate-change policies. Are there, in fact, alternatives to the scheme of tradable emissions permits embodied in the Protocol? The fact is that alternative approaches have not had a serious hearing among natural scientists or among policymakers. What are some alternatives? For global public goods, there are three potential approaches: command-and-control regulation, quantity-oriented market approaches, and taxor price-based regimes. Of these, only the tradable-quantity and the price-like regimes have any hope of being reasonably efficient. Under a tradable-quantity approach, an agreement proceeds by setting limits on emissions by different countries. The limits are partially or wholly transferable among countries. This is the approach taken under the Kyoto Protocol. This approach has very limited international experience under existing protocols such as the CFC (chlorofluorocarbon) mechanisms and somewhat broader experience under national trading regimes, such as the U.S. sulfur dioxide regime. A radically different approach is to use harmonized prices, fees, or taxes as a method of coordinating policies among countries. This approach has no international experience in the environmental area, although it has modest experience nationally in such areas as the U.S. tax on ozone-depleting chemicals. On the other hand, the use of harmonized, price-type measures has extensive international experience in fiscal and trade policies, such as with the harmonization of taxes in the European Union and harmonized tariffs in international trade. These thoughts on the structure of international agreements to control global warming should not be regarded as negotiating strategies